7 Risk factors for patellofemoral pain: a systematic review & meta-analysis. (19th April 2018) - Neal, Bradley; Lack, Simon; Lankhorst, Nienke; Raye, Andrew; Morrissey, Dylan; Middelkoop, Marienke Van
Abstract : Introduction: Patellofemoral pain (PFP) is common amongst active individuals and has significant negative impact upon quality of life. In order to reduce PFP incidence, an improved understanding of risk factors is essential. Materials and methods: Medline, Web of Science and SCOPUS were searched for prospective studies analysing at least 1 potential risk factor for PFP development. Two independent assessors graded study quality and data were pooled where appropriate. Results: 18 studies were included, involving 4818 participants. 483 participants developed subsequent PFP, an incidence of 11%. 3 distinct homogenous subgroups were identified; including military recruits (incidence 11%), adolescents (incidence 11%) and recreational runners (incidence 6%). Moderate quality evidence indicates that low baseline quadriceps strength, measured concentrically or normalised anthropometrically using an isokinetic dynamometer, is a risk factor for PFP development in military recruits (SMD −0.69, CI: −1.02 to −0.35). There is moderate quality evidence that higher baseline hip abduction strength, measured with a hand-held dynamometer, is a risk factor for PFP development in adolescents (SMD 0.71, CI: 0.39 to 1.04). Multiple variables of interest, including participant height, weight, BMI, body fat percentage, age and Q-angle, were not found to be risk factors for PFP development in any cohort. Conclusion: This review identifies multiple variables that do not predict PFP development, but shows quadriceps weakness in military recruits and increased hip strength in adolescents are risk factors for PFP. Large-scale prospective studies, perhaps involving novel study designs, are urgently warranted in the light of the consistently poor long-term outcomes of clinical trials.